1999
DOI: 10.1111/j.1572-0241.1999.01062.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Immediate Complications After Progressive Pneumatic Dilation for Achalasia

Abstract: This study showed a low prevalence of early complications using this progressive technique. Patients with hiatal hernia, esophageal diverticulum, or vigorous achalasia may safely undergo progressive pneumatic dilation. Only patients older than 90 yr should be referred for progressive pneumatic dilation with caution. Most of perforations arose during the first dilation, but there was no predictive pretherapeutic factor of perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 21 publications
2
31
0
5
Order By: Relevance
“…159 A study of the complications arising from 504 balloon dilations in 237 patients with achalasia revealed 4 (1.7%) asymptomatic haematomas, but no clinically significant haemorrhage. 160 There were, however, 7 (3%) perforations. Seven case series have reported no haemorrhages following ileal or colonic dilation.…”
Section: Dilatationmentioning
confidence: 95%
“…159 A study of the complications arising from 504 balloon dilations in 237 patients with achalasia revealed 4 (1.7%) asymptomatic haematomas, but no clinically significant haemorrhage. 160 There were, however, 7 (3%) perforations. Seven case series have reported no haemorrhages following ileal or colonic dilation.…”
Section: Dilatationmentioning
confidence: 95%
“…Some patients respond to conservative treatment with antibiotics and parenteral nutrition but others need a surgical repair. Other complications of pneumatic dilation include development of intramural hematomas, esophageal mucosal tears, and diverticula at the gastric cardia [72] . Severe transient and intermittent postprocedural chest pain has been reported in approximately 15% of patients during the 24-48 h after dilation [73,74] .…”
Section: Pneumatic Dilationmentioning
confidence: 99%
“…18,38,[51][52][53] It has been noted that the risk of perforation is greatest on the initial dilatation as opposed to subsequent dilatations. 52,53 Evaluation of predictive factors for perforation revealed that high distal oesophageal contraction amplitudes (>70 cm H 2 O) were more predominant in those with subsequent perforation. 52 Gastro-oesophageal reflux (GER) occurs in approximately 4-16% of patients after pneumatic dilatation.…”
mentioning
confidence: 99%